2013
DOI: 10.1097/mou.0b013e328361d3ed
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant radiotherapy or early salvage radiotherapy in pT3R0 or pT3R1 prostate cancer

Abstract: The alternative ART or surveillance along with SRT after prostatectomy cannot yet be decided on conclusively. Compliance, physical side-effects, psychological aspects and life expectancy should be taken into account when discussing treatment options. Ongoing and planned trials will hopefully identify subgroups that profit most from one or the other strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
0
3
0
3
Order By: Relevance
“…Single-modality therapy involving surgery alone might be of limited use in patients with stage pT3N0M0 prostate cancer, and a multimodal approach may be more beneficial. Three studies found that adjuvant radiotherapy after radical prostatectomy reduced the risk of subsequent biochemical recurrence in randomized clinical trials [5-7]. Thompson et al reported a survival benefit of adjuvant radiotherapy, with a 10-year estimated survival rate of 74% in 214 patients with pT2-3 N0 prostate cancer treated with adjuvant radiotherapy, compared with 66% in 211 cases treated with surgery alone, after median follow-up period of 12.5 years [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Single-modality therapy involving surgery alone might be of limited use in patients with stage pT3N0M0 prostate cancer, and a multimodal approach may be more beneficial. Three studies found that adjuvant radiotherapy after radical prostatectomy reduced the risk of subsequent biochemical recurrence in randomized clinical trials [5-7]. Thompson et al reported a survival benefit of adjuvant radiotherapy, with a 10-year estimated survival rate of 74% in 214 patients with pT2-3 N0 prostate cancer treated with adjuvant radiotherapy, compared with 66% in 211 cases treated with surgery alone, after median follow-up period of 12.5 years [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…1800 hastanın dahil edildiği 3 randomize prospektif çalışmanın analizinde, cerrahi sınır pozitifliği olan hastalarda, cerrahi sonrası adjuvan RT ile tedavinin hastanın cerrahi sonrası aktif takibe alınması ile arasında klinik ve istatistiksel açıdan üstünlüğü olduğu kadar yan etki profili açısından da daha fazla zararı olduğu gösterildi (29,30). Rektal komplikasyonlar, üretral darlık ve total üriner inkontinans oranları sadece cerrahi tedavi alan ve sadece takip olanlara nispeten daha fazlaydı.…”
Section: Adjuvan Rtunclassified
“…La radioterapia di salvataggio (SRT) apre una seconda possibilità di cura per la recidiva locale e per i pazienti con PSA rilevabile dopo chirurgia: oltre il 60% può riportarsi ad un PSA nel range di normalità (6568) e l'80% può essere libero da progressione a 5 anni (67): valori di PSA pre-RT inferiori a 0,5 ng/mL sono associati con una sopravvivenza libera da recidiva significativamente superiore (66, 69). Studi clinici prospettici randomizzati, in corso, RADICALS (70), GETUG-17/0702 (71) e RAVES TROG 08-03 (72), confrontano ART e SRT considerando anche il beneficio aggiuntivo dalla terapia ormonale: essi contribuiranno a chiarire l'impatto della radioterapia adiuvante rispetto al salvataggio, il valore relativo della combinazione RT-terapie ormonali, e a rendere chiaro quali pazienti ne trarranno beneficio (49).…”
Section: Indicazioniunclassified
“…Le tecnologie a disposizione, infine, dovrebbero consentire un'ulteriore riduzione degli effetti collaterali, peraltro già contenuti (65, 77), anche con dosi decisamente superiori ai 70 Gy (78, 79).…”
Section: Indicazioniunclassified